Arquitetura hostil em Santa Maria: do patrimônio material à desigualdade social - Piccolli, Dailza Fiuza (2024)
The Hostile Architecture as an excludent social practice is perceived increasingly on urban spaces in different cities and besides restricting the access and uses of specific places, it also affects the relationship between Citizen and City, including on the heritage and touristic aspect. Therefore, this study, developed on the environment of the Post Graduation in Cultural Heritage Program of UFSM in History and Cultural Heritage line of research, seeks to analyze the hostile Architecture manifestations on Avenida Rio Branco in Santa Maria, associated with material Heritage. For that, it was used a methodology that involves bibliographic and field researches, once that it is classified as exploratorydescriptive, in a way which its results show the identification of four exemples of Hostile Architecture on historical Buildings on Avenida Rio Branco. Besides, as a way of complementing the study, it was elaborated a Folder about the topic, as a way of turning the knowledge about hostile Architecture clear and accessible, this material succinctly explains what hostile architecture is and its most common forms of materialization, as well as showing examples found in some parts of the city of Santa Maria (RS).